PD-L1 targeting high-affinity NK (t-haNK) cells induce direct antitumor effects and target suppressive MDSC populations - Jeffrey Schlom; James W Hodge; Clint T. Allen; Shahrooz Rabizadeh; Patrick Soon-Shiong; John H. Lee; Renee N. Donahue; Kristen Solocinski; Michelle R Padget; Kellsye P Fabian; Yvette Robbins (Journal for ImmunoTherapy of Cancer)
Background Although immune checkpoint inhibitors have revolutionized cancer treatment, clinical benefit with this class of agents has been limited to a subset of patients. Hence, more effective means to target tumor cells that express immune checkpoint molecules should be developed. For the first time, we report a novel natural killer (NK) cell line, programmed death-ligand 1 (PD-L1) targeting high-affinity natural killer (t-haNK), which was derived from NK-92 and was engineered to express high-affinity CD16, endoplasmic reticulum-retained interleukin (IL)-2, and a PD-L1-specific chimeric antigen receptor (CAR). We show that PD-L1 t-haNK cells also retained the expression of native NK receptors and carried a high content of granzyme and perforin granules.Methods NanoString, flow cytometry, and immunofluorescence analyses were performed to characterize the phenotype of irradiated PD-L1 t-haNK cells. In vitro PD-L1 t-haNK cell activity against cancer cell lines and human peripheral blood mononuclear cells (PBMCs) was determined via flow-based and 111In-release killing assays. The antitumor effect of PD-L1 t-haNK cells in vivo was investigated using MDA-MB-231, H460, and HTB1 xenograft models in NOD-scid IL2Rgammanull (NSG) mice. Additionally, the antitumor effect of PD-L1 t-haNK cells, in combination with anti-PD-1 and N-803, an IL-15 superagonist, was evaluated using mouse oral cancer 1 syngeneic model in C57BL/6 mice.Results We show that PD-L1 t-haNK cells expressed PD-L1-targeting CAR and CD16, retained the expression of native NK receptors, and carried a high content of granzyme and perforin granules. In vitro, we demonstrate the ability of irradiated PD-L1 t-haNK cells to lyse 20 of the 20 human cancer cell lines tested, including triple negative breast cancer (TNBC) and lung, urogenital, and gastric cancer cells. The cytotoxicity of PD-L1 t-haNK cells was correlated to the PD-L1 expression of the tumor targets and can be improved by pretreating the targets with interferon (IFN)-γ. In vivo, irradiated PD-L1 t-haNK cells inhibited the growth of engrafted TNBC and lung and bladder tumors in NSG mice. The combination of PD-L1 t-haNK cells with N-803 and anti-PD-1 antibody resulted in superior tumor growth control of engrafted oral cavity squamous carcinoma tumors in C57BL/6 mice. In addition, when cocultured with human PBMCs, PD-L1 t-haNK cells preferentially lysed the myeloid-derived suppressor cell population but not other immune cell types.Conclusion These studies demonstrate the antitumor efficacy of PD-L1 t-haNK cells and provide a rationale for the potential use of these cells in clinical studies.